THE INFLUENCE OF POSITIVE EMOTION ON IMPULSE BUYING WITH STORE ATMOSPHERE AS A MODERATING VARIABLE - Nurhayati, Ade; Raheni, Cahyaning; Arief, Syarifuddin; Maulana, Indra; Sari, Efti Novita (ITB AAS Indonesia Surakarta, 2024)
Abstract Researchers believe that Positive Emotions can significantly influence the Impulse Buying variable because the more emotional a person is, the more emotional they are because they have no financial problems, get good religious and social studies, and have a happy family who no longer think about prices when shopping. Apart from that, researchers also have a second belief, namely that the Store Atmosphere variable is able to moderate these two variables. This research is quantitative research with an exploratory approach. The data collected in this research used a questionnaire method for 300 people who had incomes above 20 million. This data is called primary data. The data used and collected were analyzed with Smart PLS 4.0. The research results showed that the Positive Emotions variable had a positive relationship and a significant influence on Impulsive Buying and the Store Atmpaoshere variable could moderate the relationship between these two variables. Keywords : Emotion Positive, Buying Impulse, Store Atmosphere